A Trip Upstream to Mitigate Marine Plastic Pollution – A Perspective Focused on the MSFD and WFD - Black, Jeffrey E.; Kopke, Kathrin; O’Mahony, Cathal (Frontiers in Marine Science, 2019)
Developing and implementing effective legislation to combat plastic litter in the marine environment has proven a significant challenge. This is in large part due to an incomplete understanding of the sources and transport pathways of plastic litter, and is manifested in Europe’s current disjointed legislative structure that governs the aquatic environment. In this article, the authors present the perspective that marine plastic pollution in European waters cannot be mitigated without increased regional integration between the dominant legislative structures, and must provide specific considerations for the role rivers and land-based activities play in the accumulation of plastic litter in the marine environment.